Android-Based Childcare Booklet as an Educational Medium to Improve Mothers’ Knowledge and Attitudes - Resna Litasari; Neli Sunarni; Aulia Ridla Fauzi; Sandriani (JURNAL KESEHATAN STIKes MUHAMMADIYAH CIAMIS, 2025)
The knowledge and attitudes of mothers as primary caregivers are key factors in implementing optimal parenting patterns. The use of technology-based educational media, such as Android-based booklets, is one innovation in maternal and child health education. This study aims to determine the effect of education using Android-based parenting booklets on improving the knowledge and attitudes of mothers of toddlers. This study is a quantitative study with a pre-experimental one-group pretest-posttest design. The study sample consisted of 60 mothers who had children aged 37–60 months at the Lembah Medina Health Centre in Ciamis Regency and were selected using total sampling technique. The research instruments were questionnaires on mothers' knowledge and attitudes. Data analysis was performed using the Friedman test. The results showed an increase in mothers' knowledge from the adequate category (65.0%) to the good category (90.0%) and a change in attitude from poor (60.0%) to positive (93.3%) after the intervention. The Friedman test showed a significant difference before and after the intervention (p < 0.05). It was concluded that the Android-based child care booklet was effective as an educational medium for improving the knowledge and attitudes of mothers of toddlers.